PERHITUNGAN KEUNTUNGAN PEMBIAYAAN MUDHARABAH DAN PEMBIAYAAN MUSYARAKAH PADA BMT KEMITRAAN DOMPET DHUAFA BOJONEGORO - LAILY ALFI SYAHRI, NUR Alfi (Jurnal Akuntansi AKUNESA, 2014)
BMT in Indonesia is growing rapidly into the rural areas, data from the PINKUB - Departement of UMKM and Cooperatives, the number of BMT in Bojonegoro district are 375 BMTs. Communities who need for financial capitals prefer BMT than Bank’s because the easiness reason of operation. BMTs have Mudharabah financing and Musyarakah financing, but they are not familiar with both products. Therefore, this study's purpose is to know how the mechanism of Mudharabah financing and Musyarakah financing calculations in BMT Kemitraan Dompet Dhuafa Bojonegoro, and the profit payments to customers. This study uses qualitative methods with case study approach. The results showed that Musyarakah financing is more profitable for customers because profit shared that received to customers is greater than the Mudharabah one.Key words: BMT, Financing, Mudharabah, Musyarakah, Profit Sharing